CONTINUANCE USE OF MANAGEMENT INFORMATION SYSTEMS FOR CIVIL REGISTRATION SERVICES - Ghina Fitri Ariesta Susilo; Panji Afandi (JRAK, 2021)
Department of Population and Civil Registration of Magelang City is a local government agency that run public services effectively and efficiently. It is because the service is oriented to the societies. This study aims to analyze supporting technology as performance support of the Department of Population and Civil Registration of Magelang City namely the Management Information System for Admissions Management of Population Administration Applications (SIMP3AK). This study belongs to the category of qualitative research. This study used interview as its method. The results show that the continuance usage of SIMP3AK is determined by the existence of three indicators, namely, trust, efficiency and effectiveness, and satisfaction.